PENGARUH KEMAMPUAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS PERKEBUNAN KABUPATEN MUSI BANYUASIN - Desi Ulpa Anggraini; Heriyana Heriyana; Iryanto Ir (Jurnal Manajemen Kompeten, 2020)
Not many work achievements achieved by employees due to employees who do not understand the main tasks and functions as well as technical training of employees are not in accordance with the main tasks and functions of each sub section or part of the reason for this research. The population is all employees of the Musi Banyuasin District Plantation Office, with a sample of 91 people using musting sampling techniques. Data management techniques used the SPSS (Statistical Product and service solutions) version 16.00 program and tested it with a simple linear regression equation. Regression calculation results can be seen that the coefficient of determination R2 obtained by 0.628. This means that 62.80% of variations in work performance variables can be explained by work ability variables while the remaining 37.20% is explained by other variables not analyzed in this study. The results of statistical calculations show the value of t count = 2.443. By using a 0.05 significance level, the calculated t value of 2.443> t table of 1.986 is obtained. So Ho was rejected and accepted Ha, meaning that work ability affected the work performance of employees at the Musi Banyuasin District Plantation Office.